PHOBIA AND ITS EFFECT ON THE ACADEMIC ACHIEVEMENT OF PHYSICS STUDENTS IN IMO STATE, NIGERIA - Ihekwaba, Chinyere (Advances in Social Sciences Research Journal, 2020)
This research studied phobia and its effect on the academic achievement of Senior Secondary School Students of Physics in Owerri Municipal Council Area of Imo State, Nigeria. A sample of 488 students (259 females and 229 males) were taken from four (4) different schools in Owerri Municipal (two co-educational and two non-educational). Data was collected using a Physics Phobia Scale (PPS) developed by the researchers and validated by experts in Measurement and Evaluation from which the phobia levels of the students were ascertained. The students’ third term results were also used as secondary data. Using the PPS score and the achievement score, the correlation coefficient, mean, and standard deviation were obtained and T-tests were run for analysis. It was found that a significant negative relationship exist between the students’ phobia score and their achievement score. Results also showed that the male students with high phobia performed better than the female students with high phobia and also that the female students had higher phobia than the males; though, the mean difference is however not significant. It is recommended that varying teaching methods and grouping students when teaching will help reduce the phobia level.